Upaya Meningkatkan Pendidikan Anak-Anak melalui KKN Mengajar - Septiadi Bleedo; Yuni Wahidah; Inggit Garnasih (Politeknik Negeri Samarinda, 2023)
Education is an effort to increase human resources to create an advanced and competitive nation. We can measure the level of education in Indonesia as still lacking or not yet optimal. Millions of children in remote areas are still unable to access education. To deal with this problem, there needs to be strong regulations from the government to provide justice to all Indonesian people to get the same education between the rich and the poor, between the rich and the poor. The background to the preparation of this work program was students' concern for children who are still in PAUD, Kindergarten or Elementary School. Considering that nowadays, most children tend to watch cellphones more often than study. It could be said that children learn only during school hours. Learning in Kindergarten cannot be separated from the introduction of letters and numbers. Introducing letters and numbers is the most basic lesson taught by an educator. Knowing letters and numbers is very important for children, because it can stimulate children's ability to learn to read and count.